Spatial inequalities in education in Northern Norway - Exploring rural-urban differences in teacher’s work experiences - Rød, Daniel Andre Voll (UiT Norges arktiske universitet, 2021)
The focus of this thesis, Spatial inequalities in education in Northern Norway -Exploring rural-urban differences in teacher’s work experiences, is on teachers’ work experiences in different geographic contexts in Norway. It explores the constraints and enablements that teachers may experience due to unequal structural conditions for education. The theoretical framework is based on critical realism and Margaret Archer’s morphogenetic approach as well as discussions of centralised versus decentralised educational systems. The data material is based on participant observation in a rural case municipality and qualitative interviews of teachers in both a rural and an urban case municipality in 2018. This thesis categorises the structural properties that constrain and enable especially rural teachers into five categories: (1) the centralised education system, (2) rural demography, (3) resource distribution among rural and urban schools, (4) local opportunity structures, and (5) spatially unaware curriculum and educational policy. The thesis shows that a centralised educational system with a centralised funding system of education, together with other structural properties like rural demography, create unequal conditions for teaching based on geography, with rural areas as the losing part vis-à-vis urban areas. The analysis is also suggesting how these conditions may be changed in order to achieve more equal conditions in education.